Multi-microgrid marketized transaction models and algorithms based on smart contracts - Fen LI; Jin LI; Songqi WU; Senlin ZHANG; Yueming LU (网络与信息安全学报)
Facing the problems of high cost,low efficiency and low transparency existing in the traditional transmission and distribution networks under the centralized management,and the demand for maximizing the interests of all players in the multi-microgrid system,a fair bidding rule and multi-objective dynamic planning model were established.Using blockchain trusted ledger and smart contract technology,a decentralized,transparent,open and information symmetrical market-oriented transaction model was established to ensure the interests of all parties.The simulation results show that the model allocation strategy can effectively balance the interests of market participants,and verify the applicability and effectiveness of the bidding rules in multi microgrid market-oriented transaction.